Paris for one and other stories - Moyes, Jojo, 1969- (New York, New York : Pamela Dorman Books, Viking, an imprint of Penguin Random House LLC, 2016)
Nell knows travelling abroad isn't really her thing, but when her boyfriend fails to show up for their romantic Paris vacation, Nell has the opportunity to prove everyone--including herself--wrong. In the eight other stories, Jojo Moyes gives us a cast of strong, relatable women in the midst of their everyday lives.
Paris for one -- Between the tweets -- Love in the afternoon -- A bird in the hand -- Crocodile shoes -- Holdups -- Last year's coat -- Thirteen days with John C -- The Christmas list.
Keywords: Young women -- Fiction; Paris (France) -- Fiction